Vivianite-induced peroxymonosulfate activation for containment removal under dark conditions: Performance, mechanism and regeneration. (15th April 2023) - Li, Qi; Wang, Mingzhou; Chen, Jia-Qi; Liu, Xiaomeng; Wang, Jing; Mu, Yang
Highlights: Vivianite effectively activated PMS for pollutant removal under dark conditions. SO4 ·− was the major response for pollutant degradation in the vivianite-PMS system. PMS preferred to bind to the Fe sites on the surface of vivianite in a bridge position. Vivianite could be efficiently regenerated by either chemical or biological reduction. Abstract: The performance and intrinsic mechanism of vivianite, a natural mineral containing structural Fe(II), for peroxymonosulfate (PMS) activation and pollutant degradation under dark conditions were comprehensively explored in this study. It was found that vivianite was able to efficiently activate PMS to degrade various pharmaceutical pollutants under dark conditions, in which the corresponding reaction rate constant of ciprofloxacin (CIP) degradation was 47- and 32-fold higher than that of magnetite and siderite, respectively. SO4 ·−, · OH, Fe(IV) and electron-transfer processes were found in the vivianite-PMS system, while SO4 ·− was the main contributor to CIP degradation. Moreover, mechanistic explorations revealed that the Fe site on the surface of vivianite could bind PMS in the form of a bridge position, and thus vivianite could rapidly activate absorbed PMS due to its strong electron-donating ability. Additionally, it was illustrated that the used vivianite could be efficiently regenerated by either chemical or biological reduction. This study may provide an alternative application of vivianite in addition to phosphorus recovery from wastewater. Graphical abstract: Image, graphical abstract